2014
DOI: 10.1071/cp13303
|View full text |Cite
|
Sign up to set email alerts
|

Common beans, biodiversity, and multiple stresses: challenges of drought resistance in tropical soils

Abstract: Common bean (Phaseolus vulgaris L.) is the grain legume with the highest volume of direct human consumption in the world, and is the most important legume throughout Eastern and Southern Africa, cultivated over an area of ~4 million ha. In Sub-Saharan Africa (SSA) drought is the most important production risk, potentially affecting as much as one-third of the production area. Both terminal and intermittent drought prevail in different production regions. The Pan-African Bean Research Alliance (PABRA), coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 48 publications
3
91
0
6
Order By: Relevance
“…Thus, a vigorous and deeper root system, with rapid growth rate is useful but not enough to have resistance to drought in common bean. Our results indicate that for water spender type of genotypes, a strategic combination of root and shoot traits such as deep root system combined with the ability to remobilize photosynthates from vegetative structures to the pods and subsequently to grain production could contribute to superior performance under intermittent drought stress (Beebe et al 2014;Rao 2014). It also appears that for water saving genotypes, with a combination of development of fine root system with high water use efficiency mechanisms at leaf level will contribute to improved adaptation to prolonged or terminal drought stress (Polania et al 2016a).…”
Section: Relationship Between Root Vigor and Shoot Traits Including Gmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, a vigorous and deeper root system, with rapid growth rate is useful but not enough to have resistance to drought in common bean. Our results indicate that for water spender type of genotypes, a strategic combination of root and shoot traits such as deep root system combined with the ability to remobilize photosynthates from vegetative structures to the pods and subsequently to grain production could contribute to superior performance under intermittent drought stress (Beebe et al 2014;Rao 2014). It also appears that for water saving genotypes, with a combination of development of fine root system with high water use efficiency mechanisms at leaf level will contribute to improved adaptation to prolonged or terminal drought stress (Polania et al 2016a).…”
Section: Relationship Between Root Vigor and Shoot Traits Including Gmentioning
confidence: 99%
“…Genotypes with superior grain yield under drought stress under field conditions and classified as water spenders (Polania et al 2016a) showed higher root vigor with deeper rooting ability under drought stress in the greenhouse. Deep roots may develop from the basal roots that change their root angle to turn downward, or from lateral roots that develop from a tap root, or both (Bonser et al 1996;Ho et al 2005;Basu et al 2007;Lynch 2011;Miguel et al 2013;Beebe et al 2014;Burridge et al 2016). High root vigor and deeper rooting ability in water spender type genotypes allows the plant to access greater amounts of available water, permitting the processes of gas exchange to continue, with the accumulation of water soluble carbohydrates in the stem and their subsequent remobilization to grain filling as was observed in some wheat genotypes (Lopes and Reynolds 2010).…”
Section: Genotypic Differences In Root Vigor and Its Relationship Witmentioning
confidence: 99%
See 2 more Smart Citations
“…Common bean (Phaseolus vulgaris L.) is the most important grain legume in Uganda (Beebe et al, 2014) and is produced primarily by smallholder farmers (Ugen et al, 2002). About two decades ago, per capita bean consumption in Uganda exceeded 50 kg year -1 in some regions (Wortmann et al, 1998a), but more recent countrywide consumption averages about 11 to 16 kg person -1 year -1 (Broughton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%